Carbide Derived Carbon (CDC) as novel adsorbent for ibuprofen removal from synthetic water and treated sewage effluent - Ismail W. Almanassra (14151321) (2022)
Purpose Pharmaceuticals are becoming one of the largest environmental concerns when it comes to the water treatment industry. Increased usage of these chemicals poses a serious risk to ecology and human health due to their leakage into surface waters. In the present study, carbide derived carbon (CDC) was used for the first time as a new adsorbent to remove ibuprofen from synthetic water and wastewater effluent. Methods The morphology, chemical composition, surface area and surface charge of the CDC particles were investigated using the transmission electron microscopy, scanning electron microscopy, energy dispersive spectroscopy, Fourier transform infrared spectroscopy, BET analysis and zeta potential measurements. The effects of CDC dosage, temperature, initial pH and agitation speed on the adsorption process were examined by using batch adsorption experiments. Moreover, the adsorption kinetics, thermodynamics, and isotherms were investigated. Results Adsorption and kinetic equilibrium data demonstrate that the adsorption of ibuprofen onto the CDC obeys the Langmuir isotherm model and the kinetics follow the pseudo-2nd order mechanism. The thermodynamic results reveal that ibuprofen adsorption is endothermic and spontaneous. The ibuprofen removal by CDC was mainly controlled by the electrostatic forces at high pH of the feed solution and by the dispersive interactions in acidic media. The ibuprofen removal is promoted at high temperature, high agitation speed and low pH. The highest adsorption capacity of ibuprofen onto the CDC was 367 mg/g at pH 3. Furthermore, the CDC efficiently removed ibuprofen from spiked treated sewage effluent. Conclusions The obtained data indicate that the CDC provides a fast and efficient adsorptive removal of ibuprofen both from a model aqueous solution and treated sewage effluent. Other Information Published in: Journal of Environmental Health Science and Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s40201-020-00554-0